2021
DOI: 10.1080/17408989.2021.1891211
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ perceptions of sport education: A response to precarity through a pedagogy of affect

Abstract: The aim of this study was to investigate coaches' perceptions of using sport education (SE) for the first time with socially vulnerable children in order explore its suitability for equipping young people living in precarity with the skills they need to take positive action to challenge their socially vulnerable backgrounds. In doing so, we want to explore what experiences of learning to use SE these coaches had, and what their perspectives of the children's learning were. Settings and participants:The study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…Colpbol, an alternative game that was unfamiliar to the students, broke with the dynamics of sports traditionally perceived as masculine. Thus, engagement in sport was not affected by the dominant position of boys versus the subordination of girls (Connell, 2005), and more opportunities were generated to develop girls' abilities through a more positive playing environment, which encouraged their empowerment (García López & Kirk, 2021;Jennings et al, 2006). This is in line with the findings of the study by Llanos Muñoz et al (2022), who reported that the novelty of implementing an alternative game reduced students' levels of frustration and enhanced their satisfaction.…”
Section: "You Can Play the Same As Them": Empowering The Girlssupporting
confidence: 57%
See 1 more Smart Citation
“…Colpbol, an alternative game that was unfamiliar to the students, broke with the dynamics of sports traditionally perceived as masculine. Thus, engagement in sport was not affected by the dominant position of boys versus the subordination of girls (Connell, 2005), and more opportunities were generated to develop girls' abilities through a more positive playing environment, which encouraged their empowerment (García López & Kirk, 2021;Jennings et al, 2006). This is in line with the findings of the study by Llanos Muñoz et al (2022), who reported that the novelty of implementing an alternative game reduced students' levels of frustration and enhanced their satisfaction.…”
Section: "You Can Play the Same As Them": Empowering The Girlssupporting
confidence: 57%
“…As one of the findings of the foundation phase was the girls' disinterest in sports with a notably masculine tradition, such as football, and their consequent lack of active participation in the classes, the development of a DU based on the alternative sport known as colpbol was proposed. Following the recommendations of García López & Kirk (2021), this is a game where there was little difference in prior knowledge between the boys and girls, with no influence from the media, and which also involved less physical contact. Colpbol consequently presented the girls with a type of invasion game with a more neutral context, thus overcoming the prejudices they had about such sports, which they identified with football.…”
Section: "You Can Play the Same As Them": Empowering The Girlsmentioning
confidence: 99%
“…It, of course, also impacts early childhood development, specifically children's socio-emotional development. Children's central social and emotional attitudes are tolerance (empathy), association attitudes, problem-solving and positive attitudes (Ananda & Fadhilaturrahmi, 2018;García López & Kirk, 2022;Marinoni et al, 2022). In simple terms, children from an early age can be accustomed to adapting, being social in their environment and expressing what they feel.…”
Section: Introductionmentioning
confidence: 99%
“…Una exposición prolongada al modelo puede disminuir las conductas antideportivas (Wahl-Alexander, Sinelnikov y Curtner-Smith, 2016), aunque aquellos participantes con un alto nivel de habilidad mostraban conductas antideportivas cuando comenzaba la competición (Schwamberger, 2015). El modelo ha llegado a utilizarse con éxito en entornos de vulnerabilidad social (i. e. García López y Kirk, 2021aKirk, , 2021b. Para lograr estos beneficios en el desarrollo moral y social del alumnado es determinante el papel del docente, creando entornos adecuados para el desarrollo de estos aspectos (Schwanberger, Wahl-Alexander y Ressler, 2017).…”
Section: Introductionunclassified